Differential virus host-ranges of the Fuselloviridae of hyperthermophilic Archaea: implications for evolution in extreme environments - Ceballos, Ruben Michael; Marceau, Caleb D.; Marceau, Joshua O.; Morris, Steven; Clore, Adam J.; Stedman, Kenneth M. (Frontiers in Microbiology, 2012)
An emerging model for investigating virus-host interactions in hyperthermophilic Archaea is the Fusellovirus-Sulfolobus system. The host, Sulfolobus, is a hyperthermophilic acidophile endemic to sulfuric hot springs worldwide. The Fuselloviruses, also known as Sulfolobus Spindle-shaped Viruses (SSVs), are “lemon” or “spindle”-shaped double-stranded DNA viruses, which are also found worldwide. Although a few studies have addressed the host-range for the type virus, Sulfolobus Spindle-shaped Virus 1 (SSV1), using common Sulfolobus strains, a comprehensive host-range study for SSV-Sulfolobus systems has not been performed. Herein, we examine six bona fide SSV strains (SSV1, SSV2, SSV3, SSVL1, SSVK1, SSVRH) and their respective infection characteristics on multiple hosts from the family Sulfolobaceae. A spot-on-lawn or “halo” assay was employed to determine SSV infectivity (and host susceptibility) in parallel challenges of multiple SSVs on a lawn of a single Sulfolobus strain. Different SSVs have different host-ranges with SSV1 exhibiting the narrowest host-range and SSVRH exhibiting the broadest host range. In contrast to previous reports, SSVs can infect hosts beyond the genus Sulfolobus. Furthermore, geography does not appear to be a reliable predictor of Sulfolobus susceptibility to infection by any given SSV. The ability for SSVs to infect susceptible Sulfolobus host does not appear to change between 65°C and 88°C (physiological range); however, very low pH appears to influence infection. Lastly, for the virus-host pairs tested the Fusellovirus-Sulfolobus system appears to exhibit host-advantage. This work provides a foundation for understanding Fusellovirus biology and virus-host coevolution in extreme ecosystems.